2002
DOI: 10.1079/bjnbjn2001509
|View full text |Cite
|
Sign up to set email alerts
|

Effect of esterified 4-desmethylsterols and -stanols or 4,4′-dimethylsterols on cholesterol and bile acid metabolism in hamsters

Abstract: 4-Desmethylsterols and -stanols reduce plasma total cholesterol (TC) and LDL cholesterol by inhibition of intestinal cholesterol absorption, while the cholesterol-lowering potential of 4,4'-dimethylsterols is less well defined. The present study aimed to compare the effects of 4-desmethylsterols, -stanols, and 4,4'-dimethylsterols on plasma and hepatic cholesterol, sterol excretion and bile acid metabolism. Male golden Syrian hamsters were fed diets containing 13 g/100 g fat, 008 g/100 g cholesterol and 0 (con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 51 publications
2
4
1
Order By: Relevance
“…The effects of sitostanol on TGs have been variable due to the different amounts of dietary cholesterol and fats used in different animal models. Similar to what was observed in the present results, Trautwein et al [32] showed a 25% decrease in TG levels by 0.48% dietary stanols in hamsters ingesting 0.08% cholesterol-containing diets.…”
Section: Discussionsupporting
confidence: 92%
“…The effects of sitostanol on TGs have been variable due to the different amounts of dietary cholesterol and fats used in different animal models. Similar to what was observed in the present results, Trautwein et al [32] showed a 25% decrease in TG levels by 0.48% dietary stanols in hamsters ingesting 0.08% cholesterol-containing diets.…”
Section: Discussionsupporting
confidence: 92%
“…In other studies in hamsters, feeding plant sterol esters has resulted in decreased total cholesterol concentrations (34)(35)(36). However, in most of these studies showing a beneficial impact of free or esterified plant sterols in hamsters, the amount of cholesterol in the diet was lower (0.08-0.09%) (34,35) than in the present experiment (0.25%). It is therefore possible that the hypercholesterolemic impact of a greater intake of cholesterol in the present study may not have been counteracted completely by plant sterol consumption.…”
Section: Figcontrasting
confidence: 72%
“…Because ferulic acid feeding did not change cholesterol excretion, it probably did not disrupt micelle formation and, thus, did not inhibit vitamin E absorption. Another possible explanation of why the oryzanol produced significantly lower plasma LPHs while reducing plasma vitamin E levels simultaneously is the possibility that oryzanol is metabolized by digestive enzymes in the GI tract of hamsters into free ferulate and free sterols [67], of which the free ferulate is then absorbed and acts as an antioxidant within the plasma, and the free sterol inhibits the cholesterol absorption within the GI tract, thereby lowering blood cholesterol levels [68,69].…”
Section: Discussionmentioning
confidence: 99%